Ribonucleotide reductase requires subunit switching in hypoxia to maintain DNA replication - Foskolou, I; Jorgensen, C; Leszczynska, K; Olcina, M; Tarhonskaya, H; Haisma, B; D'Angiolella, V; Myers, W; Domene, C; Flashman, E; Hammond, E (Elsevier, 2017)
Cells exposed to hypoxia, experience replication stress but do not accumulate DNA damage, suggesting sustained DNA replication. Ribonucleotide Reductase (RNR) is the only enzyme capable of de novo synthesis of dNTPs. However, oxygen is an essential cofactor for mammalian RNR (RRM1/RRM2 and RRM1/RRM2B), leading us to question the source of dNTPs in hypoxia. Here, we show that the RRM1/RRM2B enzyme is capable of retaining activity in hypoxia and therefore is favored over RRM1/RRM2 in order to preserve on-going replication and avoid the accumulation of DNA damage. We found two distinct mechanisms by which RRM2B maintains hypoxic activity and identified responsible residues in RRM2B. The importance of RRM2B in the response to tumor hypoxia is further illustrated by correlation of its expression with a hypoxic signature in patient samples, roles in tumor growth and radioresistance. Our data provide mechanistic insight into RNR biology, highlighting RRM2B as a hypoxic-specific, anti-cancer therapeutic target.